Analisis Tegangan Chain Pada Bucket Elevator Untuk Mencegah Troubleshoot Unit Raw Mill Indarung IV Di PT Semen Padang - Muhammad Lutfi; Nurlianna Tarigan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
Bucket elevator is a piece of equipment used to move material obliquely from the bottom to the top. At the Indarung V factory, bucket elevators are used to move the cement output from the tube mill to the sepack separator because the inlet position of the sepack separator is much higher than the oulet tube mill, which is about 20 meters. The component that often experiences failure is the chain on the bucket conveyor. After various considerations by the management at PT. Semen Padang brought back partners to replace the chain with better specifications. Finally the chain was replaced with a new one, type CNBH450-B12-A. From the calculation results it can be seen that the maximum chain tension is 34,129.83 kg, and the stress on the pin chain shaft when operating the bucket elevator in the raw mill unit is 14.798 N/m2, and the torque moment that occurs is 17.9256 N.m.